Organic matter in coal seam-VI of the Barapukuria coal field in Bangladesh - Tahsin, S; Hossain, HMZ; Hossain, MM (Bangladesh Journal of Scientific and Industrial Research, 2016)
Organic matter sources and depositional environments of Permian Gondwana coals in the coal seam-VI, Barapukuria coal field, northwestern Bangladesh have been investigated using CHNS elemental analysis. A total of 8 coal samples were collected from the coal seam-VI within depth range between 118 and 509 m. Total organic carbon (TOC), hydrogen, nitrogen and sulfur contents range from 48 to 75 (average 61 wt.%), 3.89 to 5.80 (average 4.59 wt.%), 2.87 to 3.87 (average 3.28 wt.%), and 0.19 to 0.37 wt.% (average 0.30 wt.%), respectively. C/N ratio range between 14 and 21 (average 19), and a positive correlation between TOC and TN (r = 0.51) suggested that organic matter in the coals was derived largely from terrestrial plants. However, C/S ratio values (up to 376) and scatter distribution between TOC and TS indicates the coal seam-VI was deposited in fresh water dominated inland lake environments. Bangladesh J. Sci. Ind. Res. 51(3), 221-230, 2016